Biology of tomato leafminer under laboratory conditions - Haji, Francisca Nemaura Pedrosa; Parra, José Roberto Postali; Silva, João Pereira; Batista, Jussara Gisela de Sordi (Pesquisa Agropecuaria Brasileira, 2014)
Scrobipalpula absoluta (Meyrick 1917) is an important pest of tomato in Brazil. The biology of this species was studied in laboratory at 27 ± 1°C and 33 ± 4% RH. The stock colony was started with larvae collected in the field and placed in Petri dishes which contained tomato leaves on wet filter paper. The adults were put in vials internally covered with paper and having their lids replaced by of nylon cloth, and fed with cotton scaked in a 10% sucrose solution. The results obtained in the study were as follows: pre-oviposition period 2.35 days; number of eggs per female 55.16; viability of eggs 44.46%; incubation eggs period 4.30 days; oviposition period 3.77 days; larval period 10.95 days with four stages; viability of larvae 20.97%; pupal period 6.15 days; viability of pupae 68.19%; longevity of males and females 9.69 and 11.52 days, respectively. The life cycle from egg to adult was about 38.12 days.